2019
DOI: 10.1186/s12891-019-2521-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a home-based exercise intervention on elderly patients with knee osteoarthritis: a quasi-experimental study

Abstract: Background Knee osteoarthritis (KOA) is common in elderly people, causes pain, loss of physical functioning, and disability. This was a two-arm, superiority, quasi-experimental trial. The aim of this study was to evaluate the effectiveness of a home-based exercise intervention (HBEI) to reduce KOA symptoms and improve the physical functioning of elderly patients. Methods A total of 171 elderly patients (60 years of age or older) with KOA were recruited from four communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 40 publications
(42 reference statements)
4
92
0
1
Order By: Relevance
“…Others reported that Tai Chi exercise offered to osteoarthritis patients, which has muscle strengthening effects, was effective in decreasing joint pain (Cho et al, ; Song et al, ). Consistent with former studies (Chen et al, ; Cho et al, ), the results of the present study showed that both experimental groups had decreased joint pain and joint stiffness, while their physical functioning had improved after the intervention compared to those in the control group. These three indicators (joint pain, joint stiffness, and physical functioning) are important criteria for evaluating the health status of osteoarthritis patients.…”
Section: Discussionsupporting
confidence: 93%
“…Others reported that Tai Chi exercise offered to osteoarthritis patients, which has muscle strengthening effects, was effective in decreasing joint pain (Cho et al, ; Song et al, ). Consistent with former studies (Chen et al, ; Cho et al, ), the results of the present study showed that both experimental groups had decreased joint pain and joint stiffness, while their physical functioning had improved after the intervention compared to those in the control group. These three indicators (joint pain, joint stiffness, and physical functioning) are important criteria for evaluating the health status of osteoarthritis patients.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, quadriceps strengthening is key in KOA management [22]. QSE as a widely used muscle training method [7,10,11], its effect on pain relief and functional improvement in patients with KOA was also demonstrated in our study ( Table 2). But the evaluation parameters of pain and physical function of WOMAC in intervention group improved significantly compared with that in control group during follow-up period.…”
Section: Discussionsupporting
confidence: 59%
“…Maintaining functionality is one of the main goals in OA treatment [9,33]. Good physical function benefits patients to perform daily activities and social interaction independently [7]. And then, quality of life in these patients improved correspondingly [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations